Job Portal Prototype Using Design Thinking Method: A Case Study at Djuanda University - Jabbar, Ma’shum Abdul; Encep, Muhammad; Novrian, Risfan; Fachrani, Jihan (IJISTECH (International Journal of Information System and Technology), 2024)
The importance of higher education in cultivating skilled human capital in the current global landscape cannot be overstated. The University of Djuanda is committed to closing the gap between job seekers and employers through the implementation of innovative initiatives that acknowledge the dynamic nature of career opportunities. This study focuses on the development of a Job Portal utilizing Design Thinking as a transformative method. The University of Djuanda employs Design Thinking, a renowned methodology recognized for its cognitive, innovative, and pragmatic problem-solving approaches, to gain a thorough comprehension of the needs, challenges, and preferences of its student body. The primary objective is to create a Job Portal that is relevant and satisfying, so enhancing user satisfaction and fostering long-lasting relationships, while also addressing the limitations of traditional recruitment methods. The core aspect of this approach revolves around the implementation of Design Thinking, which improves the effectiveness of problem-solving endeavors. The objective of the research is to create a Job Portal that efficiently caters to the needs of job seekers and employers by demonstrating empathy towards them. The website aims to consistently improve its features and functionalities through iterative methods of generating ideas, creating prototypes, and conducting tests. This is done to fulfil the requirements of all stakeholders involved in the recruitment process. To evaluate the user experience, a User Experience Questionnaire (UEQ) was administered to a sample of 20 participants, comprising 10 job seekers and 10 recruiters. The visualization employs a questionnaire consisting of six Likert-scale items, which encompassed a range from "Strongly Disagree" to "Strongly Agree." The results indicate a significant level of user satisfaction, affirming the effectiveness of the Design Thinking method in developing a Job Portal tailored to the diverse needs of job seekers and recruiters